Neutrophil-to-lymphocyte ratio may be a marker of peripheral artery disease complexity - Aykan, Ahmet Çağrı (Anatol J Cardiol, 2016)
OBJECTIVE: The aim of this study was to evaluate the relationship between peripheral artery disease (PAD) severity and complexity, as evaluated by TransAtlantic Inter-Society Consensus-II (TASC-II) classification, and neutrophil-to-lymphocyte (N/L) ratio. METHODS: A total of 407 patients underwent peripheral angiography due to signs and symptoms of PAD; of these, 64 patients were excluded and the remaining 343 patients were enrolled in this cross-sectional study. Patients with previous peripheral revascularizations, acute coronary syndrome, vasculitis, non-atherosclerotic stenosis, and malignancy were excluded. Patients were divided into 4 groups according to TASC-II classification, and clinical and laboratory data were compared. The chi-square test, Student’s t-test, Mann–Whitney U test, analysis of variance, Kruskal–Wallis test, Spearman’s correlation analysis, multiple logistic regression analysis, and receiver operating characteristic (ROC) curve analysis were used for statistical analysis. RESULTS: Lymphocyte count was weakly correlated (r=–0.169, p=0.002) whereas neutrophil count and N/L ratio were moderately correlated with the TASC score (r=0.432, p<0.001 and r=0.470, p<0.001, respectively). Low-density lipoprotein cholesterol [odds ratio (OR)=1.010, 95% confidence interval (CI) 95%=1.003–1.017, p=0.004], high-density lipoprotein cholesterol (OR=0.940, 95% CI=0.894–0.987, p=0.013), and N/L ratio (OR=1.914, 95% CI=1.515–2.418, p<0.001) were the independent factors for predicting a higher TASC class in multiple logistic regression analysis. The cut-off value of the N/L ratio for predicting TASC C&D class was >3.05 (sensitivity=75.0%, specificity=62.9%, area under the curve=0.678, 95% CI=0.688–0.784, p<0.001) in ROC curve analysis. CONCLUSION: The N/L ratio, a marker of inflammation, may be an important predictor of PAD complexity. Therefore, a simple blood count test may provide an important clue about the severity of PAD and risk stratification in patients presenting with intermittent claudication. Additional studies are required to confirm our findings.